Recent warming trends in Antarctica revealed by multiple reanalysis - Sai Wang; Guan-Cheng Li; Zi-Huan Zhang; Wen-Qian Zhang; Xin Wang; Deliang Chen; Wen Chen; Ming-Hu Ding (Advances in Climate Change Research, 2025)
The lack of long-term in-situ observations hampers our ability to fully understand climate change in Antarctica. State-of-the-art reanalysis datasets fill a critical gap, and this study utilizes the ensemble mean from five reanalysis datasets to examine temperature changes and their associated mechanisms in Antarctica. The findings reveal that the entire Antarctic continent has experienced significant warming from 1980 to 2023, with a statistically significant warming rate of 0.12 °C per decade at the 0.05 level. Further analysis suggests that the warming in Antarctica is primarily driven by thermodynamic processes, contributing to an increase of approximately 0.22 °C per decade. In contrast, dynamic processes have caused an overall cooling of the Antarctic continent at a rate of −0.10 °C per decade, partially offsetting the effects of thermodynamic processes. Additionally, the ensemble mean confirms a notable shift in temperature trends in the early 2000s. Finally, the study shows that in East Antarctica, dynamic processes primarily drive the shift in temperature trends, while in West Antarctica and the Antarctic Peninsula, thermodynamic processes are the main contributors. This research offers valuable insights into the complexities and mechanisms of climate change in Antarctica, emphasizing the importance of accurate predictions for future changes in this critical region.